Research communication: effects of screening colonoscopy on colorectal cancer mortality : lessons from comparative analyses of randomised trials - Brenner, Hermann; Sergeev, Dmitry; Heisser, Thomas; Hoffmeister, Michael (Alimentary pharmacology & therapeutics, 2025)
NordICC, the first randomised trial on long-term effects of screening colonoscopy, failed to demonstrate a significant reduction in colorectal cancer (CRC) mortality. We compared reported 10-year CRC mortality results from NordICC with those of NORCCAP, a similarly designed pragmatic sigmoidoscopy trial. In NORCCAP, differences in CRC mortality only began to emerge after 9.5 years of follow-up, rapidly increased thereafter and were approximately 4-fold as high after 12 years than after 10 years. Other sigmoidoscopy trials yielded similar 11- to 12-year results. Our analysis suggests that the apparent negative CRC mortality results of NordICC primarily reflect insufficient follow-up time.
Gesehen am 22.10.2025